PEMBERDAYAAN POTENSI TENUN MENUJU MASYARAKAT KERJA, MANDIRI, DAN SEJAHTERA DI DESA SIDOMULYO, KECAMATAN SELOREJO, KABUPATEN BLITAR - Eti Setiawati; Putri Kumala Dewi; Dany Ardhian; Fatmawati Fatmawati; Wahyu Widodo (Universitas Negeri Surabaya, 2018)
In Sidomulyo Village there is a weaving craft industry that has the potential to be international. This weaving industry is AJZ's weaving industry, owned by Mrs. Asih Tri Tanti, a full-time female worker. According to the results of an interview with Ms. Asih Tri Tanti on April 13, 2017, it is known that her weaving skills are currently acquired while working as a migrant worker in Brunei Darussalam. Then in 2013, this craftsman returned to Sidomulyo Village to develop the potential of weaving craft in his village. However, there were many obstacles. Finally, from 2013 to 2017, Bu Asih worked with businessmen from the Sultanate of Brunei Darussalam and had been contracted for 10 years by this country. Each sheet, this woven fabric is sold at Rp. 5,000,000. The potential of Asih bu is very likely to be developed. The development of these handicrafts can open employment opportunities from local residents and certainly improve the welfare of the community, especially vulnerable women and women with disability. This service aims to (1) increase the availability of human resources from diffable groups and vulnerable women, (2) shape the mindset of the people who have the character of independence, (3) establish coordination between the government and the community regarding the development of weaving potential, and (4) provide a place for people with disabilities who are members of PPDI to develop their skills. The method of implementation is carried out through seminars and weaving training for vulnerable women and women with disabilities. The results show that UB's community service activities in this weaving training are able to (1) improve Human Resources (HR) (disabled and vulnerable women) in Sidomulyo Village, Blitar Regency, (2) improve the mindset of the people who have the character of independence, and (3) able to change the mindset of the local community to not be ashamed to work in weaving in their own neighbors.